El ser y el tener de los habitantes de la ciudad de Medellín como determinantes de la satisfacción con la vida (2016)
This study aims to find and analyze the causal effects of various socioeconomic and demographic factors in life satisfaction of households in the city of Medellín. For this, a logistic model is estimated, categorizing into two groups the explanatory variables: the inherent aspects of being and the characteristics related with having material goods. The main results suggest that being single in relation to another marital state has a negative effect on subjective well being as well as being from African descent over another ethnic group. On the side of having, it should be noted that higher levels of education and higher socioeconomic strata increases subjective well being. It is concluded that both, the characteristics of “being” like those of “have” are fundamental to explain life satisfaction, and therefore for making public policy decisions.